2022
DOI: 10.3897/mycokeys.86.73861
|View full text |Cite
|
Sign up to set email alerts
|

New and interesting species of Penicillium (Eurotiomycetes, Aspergillaceae) in freshwater sediments from Spain

Abstract: Penicillium species are common fungi found worldwide from diverse substrates, including soil, plant debris, food products and air. Their diversity in aquatic environments is still underexplored. With the aim to explore the fungal diversity in Spanish freshwater sediments, numerous Penicillium strains were isolated using various culture-dependent techniques. A preliminary sequence analysis of the β-tubulin (tub2) gene marker allowed us to identify several interesting species of Penicillium, which were later cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 88 publications
0
7
0
Order By: Relevance
“…Sect. Lanata-Divaricata is a species-rich section in Penicillium, and about 85 species have been described hitherto [4,20,27,28,31,33]. Our phylogenetic tree indicated that P. zhanjiangense was well-located among other species of sect.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Sect. Lanata-Divaricata is a species-rich section in Penicillium, and about 85 species have been described hitherto [4,20,27,28,31,33]. Our phylogenetic tree indicated that P. zhanjiangense was well-located among other species of sect.…”
Section: Discussionmentioning
confidence: 73%
“…With the application of multiple loci phylogeny, the inter-specific relationships within these genera have become more clear [13][14][15]. Currently, the genus Aspergillus comprises 483 species belonging to 27 sections [11,[16][17][18][19][20][21][22], Penicillium contains 530 species in 33 sections [20,[22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38], and Talaromyces includes 204 species in 7 sections [6,18,32,[39][40][41][42]. They show a broad range of habitats, such as woody substratum, sandy soil, tidal flats, water, and indoor air [43][44][45][46][47].…”
Section: Introductionmentioning
confidence: 99%
“…It differs from the latter in 53 bp for BenA, 69 bp for CaM and 70 bp for RPB2. Morphologically, it differs in slower growth rate on MEA at 25 • C (25-27 vs. 41-43 mm), faster growth rate on YES (55-56 vs. 49-51 mm), terverticillate instead of biverticillate conidiophores, shorter stipes (60-125 vs. 88-215 µm), much longer metulae and phialides (9-19 vs. 5-10 µm and 8-13 vs. 6-9 µm, respectively) and larger conidia (3.0-4.5 vs. 2.0-2.5 µm) [63]. On MEA 25 • C, 7 days: Colonies nearly circular, protuberant at centers; margins narrow, entire; mycelia white; texture velutinous; sporulation dense; conidia en masse greyish green; soluble pigments absent; exudates absent; reverse orange, with a few red patches at centers.…”
Section: New Speciesmentioning
confidence: 99%
“…hispanica [32], C. fluviale [33], C. minutisporum [34], C. pilosum [35], C. submersum [34], and C. undulatum [36], and the two members of the genus Emmonsiellopsis (E.), E. coralliformis and E. terrestris [37]. All these findings and others recently published [38][39][40][41][42][43][44] indicate that freshwater sediments serve as a reservoir for a great diversity of filamentous ascomycetes, which warrant further investigation in order to address gaps in fungal phylogenetic relationships, such as has been done in the present study for some species of the order Onygenales.…”
Section: Introductionmentioning
confidence: 99%